PHACE Syndrome: A Rare Case - Taslicay, Ceylan Altintas; Dervisoglu, Elmire; Ciftci, Ercument; Corapcioglu, Funda; Anik, Yonca (Journal of Pediatric Genetics, 2020)
PHACE syndrome (OMIM 606519) is a rare neurocutaneous vascular disorder, characterized by posterior fossa malformations, large cervicofacial infantile hemangiomas, arterial anomalies, aortic coarctation, cardiac abnormalities, and eye abnormalities. The long-term outcome of PHACE syndrome patients is unclear; however, it seems that they are at risk for childhood stroke. The radiologist has an important role on diagnosis of PHACE syndrome and in the assessment of potential complications. Investigation of infants with segmental craniofacial hemangiomas should include cranial magnetic resonance imaging (MRI) and magnetic resonance angiography (MRA) of the cerebral and cervical arteries. Brain MRI and MRA findings of a 5-year-old female patient with PHACE syndrome are presented.
Keywords: childhood stroke; magnetic resonance angiography; PHACE syndrome